Assessment of barriers to the dietary adherence among type 2 diabetic patients in Pakistan: a cross-sectional study - Sukaina Shabbir; Mehreen Amer; Saba Mughal; Thamina Rashid; Habiba (Journal of the Pakistan Medical Association)
Objective: To assess the common barriers responsible for non-adherence to dietary recommendations among type 2 diabetic patients.